Migration - utopia or myopia? - Osborne, Peter (Rangifer, 1998)
Peter Osborne spent a sabbatical in northern America and was surprised that so many scientists and students stated that caribou migration was largely the result of mosquito pressure. He failed however to find any documented evidence of this claim although he was constantly confronted by the well known «facts» that mosquitoes had been observed to drive caribou crazy and even kill juveniles. The issue Osborne wishes to focus is that an experimentally unsubstantiated anthropomorphism appears to have become critical evidence in support of a theory. A recent article in Nature (393, 511-513, 1998) devoted to the uses of 'science in fiction' to stimulate thought and discussion about aspects of academia encouraged him to write the following comment in the form of a parody of ancient Greek dialogues.
Keywords: debate article; letter; migration; mosquito pressure